Association Between Cardiometabolic Comorbidity Burden and Outcomes in Heart Failure - Carine E. Hamo; Xiyue Li; Chiadi E. Ndumele; Amrita Mukhopadhyay; Samrachana Adhikari; Saul Blecker (Journal of the American Heart Association: Cardiovascular and Cerebrovascular Disease, 2025)
Background Cardiometabolic comorbidities such as obesity, diabetes, and hypertension are highly prevalent in heart failure (HF). We aimed to examine the association between severity of cardiometabolic comorbidities and hospitalization in patients with HF. Methods In a retrospective electronic health record‐based cohort of adults ≥$$ \ge $$18 with HF, we categorized individuals based on the number of severe cardiometabolic comorbidities, including hypertension, diabetes, and obesity. Severely uncontrolled comorbidities were defined as systolic blood pressure ≥160 mm Hg, hemoglobin A1c ≥8%, and body mass index ≥35 kg/m2. Cox regression models were used to assess the association between cardiometabolic comorbidity burden and time to all‐cause and HF hospitalization at 1 year, adjusting for age, sex, race or ethnicity, and insurance status, smoking, prior hospitalization, and Elixhauser comorbidity index. Stratified analyses were conducted for HF with preserved and reduced ejection fraction. Results A total of 26 800 individuals with HF (mean age 75±$$ ± $$13.7, 46% women, 69% White) experienced 4284 (16%) hospitalizations over a 1‐year period. Compared with individuals with absent comorbidities, those with 1 or 2 to 3 severely uncontrolled comorbidities had a significantly higher risk of all‐cause hospitalization (hazard ratio [HR], 1.23 [95% CI, 1.09–1.39] and HR, 1.57 [95% CI, 1.35–1.83], respectively). We found similar associations for HF hospitalization. These associations were similar among individuals with HF with preserved ejection fraction compared with HF with reduced ejection fraction. Conclusions Greater cardiometabolic comorbidity burden was associated with increased risk of all‐cause hospitalization in HF. This reinforces the role for targeting severely uncontrolled cardiometabolic comorbidities to reduce morbidity in HF.